Organoid Technology: A Reliable Developmental Biology Tool for Organ-Specific Nanotoxicity Evaluation - Prasad, Minakshi; Kumar, Rajesh; Buragohain, Lukumoni; Kumari, Ankur; Ghosh, Mayukh (Frontiers in Cell and Developmental Biology, 2021)
Engineered nanomaterials are bestowed with certain inherent physico-chemical properties unlike to their parent materials rendering them suitable into the multifaceted needs of state-of-the art biomedical and pharmaceutical applications. The log phase development of nano-science along with improved ‘bench to beside’ conversion carries enhanced probability of human exposure with numerous nanoparticles. Thus toxicity assessment of these novel nano-scale materials holdskey to ensure the safety aspects or else the global biome will certainly face a debacle. The toxicity may span from health hazard due to direct exposure to indirect means through food chain contamination or environmental pollution, even causing genotoxicity. Multiple ways of nanotoxicity evaluation includes several in-vitro and in-vivo methods; with in-vitro methods occupying bulk of the ‘experimental space’. Underlying reason may be multiple but ethical constrains in in-vivo animal experiments is a significant one. Two dimensional (2D) monoculture is undoubtedly the most exploited in-vitro method providing advantages in terms of cost-effectiveness, high throughput and reproducible. However, it often fails to mimic a tissue or organ which possesses a defined three dimensional structure (3D) along with inter-cellular communication machineries. Instead microtissues such as spheroids or organoids having a precise 3D architecture and proximate in-vivo tissue-like behavior can provide more realistic evaluation than 2D monocultures. Recent developments in microfluidics and bioreactor-based organoid synthesis have eased the difficulties to prosper nano-toxicological analysis in organoid model surpassing the obstacle of ethical issues. The present review will enlighten applications of organoids in nanotoxicological evaluation, its advantages and future prospects towards securing commonplace nano-interventions.